Physiological and Transcriptome Analysis of Iron and Phosphorus Interaction in Rice Seedlings - Zheng, Luqing (American Society of Plant Biologists, 2009)
The antagonistic interaction between iron (Fe) and phosphorus (P) has been noted in the area of plant nutrition. To understand the physiology and molecular mechanisms of this interaction, we studied the growth performance, nutrient concentration, and gene expression profiles of root and shoot segments derived from 10-d-old rice (Oryza sativa) seedlings under four different nutrient conditions: (1) full strength of Fe and P (+Fe+P); (2) full strength of P and no Fe (−Fe+P); (3) full strength of Fe and no P (+Fe−P); and (4) without both Fe and P (−Fe−P). While removal of Fe in the growth medium resulted in very low shoot and root Fe concentrations, the chlorotic symptoms and retarded seedling growth were only observed on seedlings grown in the presence of P. Microarray data showed that in roots, 7,628 transcripts were significantly changed in abundance in the absence of Fe alone. Interestingly, many of these changes were reversed if P was also absent (−Fe−P), with only approximately 15% overlapping with –Fe alone (–Fe+P). Analysis of the soluble Fe concentration in rice seedling shoots showed that P deficiency resulted in significantly increased Fe availability within the plants. The soluble Fe concentration under –Fe–P conditions was similar to that under +Fe+P conditions. These results provide evidence that the presence of P can affect Fe availability and in turn can influence the regulation of Fe-responsive genes.